2001
DOI: 10.1614/0890-037x(2001)015[0424:wcieam]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Weed Control in Established Alfalfa (Medicago sativa) with Postemergence Herbicides1

Abstract: Field experiments were conducted during 1998, 1999, and 2000 in Santa Fe, Argentina, to evaluate chlorimuron, clethodim, flumetsulam, 2,4-DB, glyphosate, and haloxyfop for control of broadleaf and grass weeds in established alfalfa. Herbicides were applied to alfalfa, 6 to 10 cm in height, after first or second cuttings. Clethodim and haloxyfop were highly effective against bermudagrass, barnyardgrass, and knotroot foxtail, and alfalfa yields were increased. 2,4-DB was effective against Scotch thistle, swinecr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…Forage quality is usually highest in weed‐free stands (7,11,15). Once alfalfa is established, other herbicides may be used, such as paraquat applied to dormant alfalfa and between cuttings (6,9), imazethapyr or a postemergent grass herbicide (2,13), or residual herbicides such as pronamide and metribuzin, depending on the production system used (8,12). Glyphosate is labeled for application to dormant alfalfa stands that are not glyphosate tolerant.…”
Section: Alfalfa Weed Controlmentioning
confidence: 99%
“…Forage quality is usually highest in weed‐free stands (7,11,15). Once alfalfa is established, other herbicides may be used, such as paraquat applied to dormant alfalfa and between cuttings (6,9), imazethapyr or a postemergent grass herbicide (2,13), or residual herbicides such as pronamide and metribuzin, depending on the production system used (8,12). Glyphosate is labeled for application to dormant alfalfa stands that are not glyphosate tolerant.…”
Section: Alfalfa Weed Controlmentioning
confidence: 99%
“…Because of this, alfalfa has a relatively constant final yield whereby the total plant dry-matter production on a given area tends to be constant regardless of species, weed or crop (Aldrich and Kremer 1997). When considering total biomass yield of forage regardless of species composition, yield is often stable since alfalfa and weeds are harvested together; thus with respect to total forage yield, weed control often appears to provide little benefit (Arregui et al 2001;Brothers et al 1994;Hall et al 1995). However, other research has shown that with moderate to severe weed infestations, alfalfa yield can be reduced through competition for light, water, and nutrients and the forage quality can be lowered by decreasing digestibility and protein content of the alfalfa hay (Cords 1973;Kapusta and Strieker 1975;Smith 1969).…”
mentioning
confidence: 99%
“…On 18 September, lucerne plants had an average of 9 nodes/ plant, with obvious fully expanded leaves, but no sign of stem extension. Arregui et al (2001) found that glyphosate application to actively growing lucerne of 6 to 10 cm in height resulted in phytotoxicity damage, which caused a yield loss, with no sign of lucerne recovery even at 70 days after treatment. Thus, although glyphosate is not registered for use on lucerne, in this experiment it was used successfully for weed control when minimal lucerne leaf area was present in winter.…”
Section: Discussionmentioning
confidence: 99%
“…Current recommendations are for a clean-up grazing in winter (late June/early July in Canterbury) followed by application of these two herbicides 10-14 days later (Cassells & Upritchard 1968;Forgie 1973;Logan & Arnst 1973;Moot et al 2003). However, glyphosate has also been used (Arregui et al 2001;Dawson 1989Dawson , 1992Wilson 1997), although it is not registered for this use. Davies et al (2003) reported that the translocation pattern of glyphosate in lucerne varied with the stage of regrowth, and found that lucerne could be killed if sprayed in early to midspring after 4-5 weeks of regrowth.…”
Section: Introductionmentioning
confidence: 99%